Distribution and environmental drivers of macrofaunal nematode communities across gradients of methane seepage at cold seeps on Hikurangi Margin (New Zealand) and potential implications of disturbance from gas hydrate extraction - Leduc, Daniel; Rowden, Ashley A.; Seabrook, Sarah; Bowden, David A.; Thurber, Andrew R.; Halliday, Jane; Law, Cliff S.; Pereira, Olivia S.; Whitten, Bethany G.; Marriner, Andrew (Frontiers in Marine Science, 2025)
Cold seeps are areas characterised by specialized biological communities that rely on chemosynthesis for their nutrition. To date, research conducted on New Zealand’s Hikurangi Margin seep communities has focused on communities at 650-1200 m water depth. Here, we characterize the macrofaunal nematode communities of New Zealand cold seeps for the first time, and at deeper (> 1200 m) seep locations (Maungaroa, Glendhu and Urutī South). There were no significant difference in nematode abundance, species richness, diversity and evenness among the seep areas, which may reflect the lack of difference in most sediment variables. However, a consistent spatial pattern in nematode abundance was observed within all the seep areas on the Hikurangi Margin: abundance was highest at or near the seep centre, decreased steeply away from the centre and was low in the periphery. These spatially consistent patterns reflect the influence of methane seepage, which appears limited to the inner 150-200 m radius of each area, on nematode abundance via input of chemosynthetic food sources. We found significant differences in nematode community structure among all three areas, with most of the heterogeneity in community structure between the shallow Urutī South area and deeper Maungaroa and Glendhu areas, and differences among nematode communities of high, medium and low abundance associated with site-specific gradients in methane seepage. Within area variability in nematode community structure was mainly correlated with food availability and sediment grain size. Consistent with previous investigations of seep nematodes, we did not find evidence of seep endemics. Although deposit feeders were generally the most abundant feeding group, there were differences in the relative abundances of different feeding groups such as microvores and epigrowth feeders among the seep areas, and as a function of distance from the centre of the seep areas. Impact on seep communities from gas hydrate extraction processes may occur via reduction or potentially cessation of free-gas methane supply to the seafloor, ‘sand’ production at the seafloor due to the physical degradation of the substrate structure, or alteration of the structural integrity of the seafloor substrate. Any spatial management options considered for managing these impacts should reflect the differences in benthic community structure between depths and locations on the Hikurangi Margin.